Myocardial Injury after Stroke - Mihalovic, Michal; Tousek, Petr (Journal of clinical medicine, 2021)
The cardiovascular system is markedly affected by stress after stroke. There is a complex interaction between the brain and heart, and the understanding of the mutual effects has increased in recent decades. Stroke is accompanied by pathological disturbances leading to autonomic dysfunction and systemic inflammation, which leads to changes in cardiomyocyte metabolism. Cardiac injury after stroke may lead to serious complications and long-term cardiac problems. Evidence suggests that blood biomarkers and electrocardiogram analyses can be valuable for estimating the severity, prognosis, and therapy strategy in patients after stroke. It is necessary to distinguish whether these abnormalities presenting in stroke patients are caused by coexisting ischemic heart disease or are caused by brain injury directly. Distinguishing the origin can have a great impact on the treatment of patients after acute stroke. In this article, we focus on epidemiology, pathophysiological mechanisms, and the presentation of cardiac changes in patients after stroke.